Implementing Integrated Holistic Education System (IHES) for Character Building at Seven Skies International School in Selangor, Malaysia - Arianto, Toni; Prayogo, Imam; Fannani, Bakhruddin; Barizi, Ahmad (International Journal Labs, 2024)
The modern educational system emphasizes not only the intellectual development of students but also the formation of moral and social character. Traditional educational systems are often perceived as inadequate in meeting the demands of globalization, technological advancement, and social change. Seven Skies International School adopts the Integrated Holistic Education System (IHES) to address these needs by incorporating intellectual, emotional, spiritual, and physical aspects into student learning. The primary challenge in implementing IHES is maintaining a balance between academic achievement and the development of students' character, as well as ensuring that educators are capable of effectively guiding emotional and spiritual growth. Common obstacles include the lack of understanding and skills among teachers in comprehensively applying IHES. This study aims to analyze the implementation of IHES at Seven Skies International School, evaluate character-building strategies, and measure their impact on students' moral and social development. The methodology employed is a qualitative approach through observation, interviews, and document analysis. The research findings indicate that IHES positively influences students' moral and social development. However, several challenges were identified in its implementation, particularly concerning teacher training and the methods used for character evaluation, which require improvement. The study's recommendations include enhancing training programs for educators and developing more comprehensive methods for character assessment.